Effectiveness and Efficiency of Seawater Evaporation Using Traditional Methods and the Innovative Flow Down System in Salt Production - Azi Wibisono Raihan; Ika Nuzula Nike; Giri D. Kartika Ary; Efendy Makhfud; Sri W. Pratiwi Wiwit (BIO Web of Conferences)
National salt demand increases every year along with the growth in demand and consumption. However, salt production decreased in 2019-2022. This encourages innovation in salt evaporation, namely the Flow Down System method, which is a seawater evaporation innovation that saves land. This research aims to analyse the process, effectiveness, and efficiency of evaporation with the Traditional method and the Flow Down System Innovation. The method used is Purposive Sampling to get statistical data processed in RStudio. The result of this research is that Flow Down System reduces land and production time compared to the traditional method. Flow Down System more effective in salt evaporation, with an average effectiveness of 98.69%-98.73% compared to the traditional 98.37%-98.69%. Flow Down’s NaCl content is (44.25%) compared traditional (-24.02%) although the traditional moisture content was slightly better (46.5% vs. 44,29%). Flow Down System more efficient 100%-time efficiency compared to traditional 33.33%. Flow Down sales efficiency 100% (IDR 239,680/month) surpassed the traditional 33.18% (IDR 79,550/month). Flow Down’s profit efficiency is 100% (IDR 105,710.32) compared to the traditional 75.25%. With 16,515 kWh of electrical energy, making it a superior method and SNI standard.